DFT investigation of H2S adsorption on graphenenanosheets and nanoribbons: Comparative study - Salih, Ehab; Ayesh, Ahmad I. (Superlattices and microstructures, 2020)
Graphenenanosheet (GNS), armchair graphenenanoribbon (AGNR), and zigzag graphenenanoribbon (ZGNR) systems were investigated by first principle calculations using the density functional theory (DFT). The DFT calculations explored the potential of utilization of these materials as gas sensors to detect hydrogen sulfide (H2S) gas. H2S gas adsorption was explored using: the adsorption energy (Eads), adsorption distance (D), charge transfer (ΔQ), density of states (DOS), and band structure of the generated systems before and after adsorption of H2S. The results showed that Eads of bare ZGNR was the highest of −0.171 eV as compared with GNS and AGNR. The surfaces of GNS, AGNR, and ZGNR have been modified with epoxy and then with a hydroxyl groups. The adsorption capacity of the three systems has been enhanced after the modifications with both the epoxy and hydroxyl groups. Based on the adsorption energy and charge transfer results, hydroxyl modified ZGNR system can be used effectively for detection applications of H2S since it exhibits the highest charge transfer and large adsorption energy. •Graphene nanosheet, armchair nanoribbon, and zigzag nanoribbon were investigated by DFT.•The materials were then used as gas sensors to detect H2S gas.•Adsorption energy, adsorption distance, charge transfer, density of states, and band structure were investigated.•The surfaces of graphene systems were modified with epoxy and hydroxyl groups.•The adsorption capacity of the three systems has been enhanced after the modifications.